Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s1570-9639(04)00065-2
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the allergenic soybean Kunitz trypsin inhibitor

Abstract: The soybean Kunitz trypsin inhibitor (SKTI) is a 21.5 kDa allergenic protein that belongs to the family of all antiparallel h-sheet proteins that are highly resistant to thermal and chemical denaturation. Spectroscopic and biochemical techniques such as circular dichroism (CD), ANS fluorescence and proteolysis were used to study its molecular structure under denaturing conditions such as acid and heat to which these allergens are commonly exposed during food processing. Reduction of native SKTI leads to its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 2 publications
1
31
0
Order By: Relevance
“…The results suggested that IgE reactivity of rAra h 2 increased, thus confirming the earlier observations of Maleki et al [30]. Roychaudhuri et al [32] have shown that soybean Kunitz trypsin inhibitor is a 21.5 kDa allergenic protein that belongs to a family of all antiparallel b-sheet proteins that are highly resistant to thermal and chemical denaturation.…”
Section: Select Examples Of Influence Of Processing On Food Allergenssupporting
confidence: 88%
“…The results suggested that IgE reactivity of rAra h 2 increased, thus confirming the earlier observations of Maleki et al [30]. Roychaudhuri et al [32] have shown that soybean Kunitz trypsin inhibitor is a 21.5 kDa allergenic protein that belongs to a family of all antiparallel b-sheet proteins that are highly resistant to thermal and chemical denaturation.…”
Section: Select Examples Of Influence Of Processing On Food Allergenssupporting
confidence: 88%
“…KSTI is highly resistant to thermal and acidic denaturation (Roychaudhuri, 2003). Thus any resistance to xenobiotics that is conferred by enhanced serine hydrolases (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For the latter, the 15S fraction corresponds to 1% of the globulins, has a high molecular mass (700 kDa) and has an isoelectric point of 4.5. Furthermore, the known proteins in soybean seeds with high allergenic potential are mainly composed of a 34-kDa maturing seed protein (also known as P34, Gly m Bd 30 K or Gly m 1) (Sewekow et al, 2008), the 23-kDa protein Gly m Bd 28 K (Xiang et al, 2004), β-conglycinin (Krishnan et al, 2009), the glycinin Gly m 6 (Holzhauser et al, 2009), lectin andlypoxygenase (L'Hocine andBoye, 2007), and a Kunitztype protease inhibitor (Roychaudhuri et al, 2004). There are also some allergenic proteins in seed shell, such as Gly m 1.0101, Gly m 1.0102, Gly m 2, Gly m 3, and SAM 22 (Gly m 4).…”
Section: Purification and Characterization Approachesmentioning
confidence: 99%